Environmental Regulation, Technological Innovation, and Industrial Transformation: An Empirical Study Based on City Function in China - Jing Xu (MDPI AG, 2021)
The Chinese economy has now transitioned from rapid expansion to high-quality growth. The issue of achieving synergy between environmental conservation and economic growth has become a serious concern. Based on the panel data of 120 prefecture-level cities in China from 2008 to 2017, we used the panel threshold regression model to investigate the influences of environmental regulation (ER) and technological innovation (TI) on urban industrial transformation. Further, we examined the threshold characteristics of four types of functional cities—resource-based, industry-oriented, comprehensive regional, and other types of cities. Our results show that ER and TI have varied effects on the industrial transformation of the four categories of functional cities. Both ER and TI have significant nonlinear threshold impacts on industrial transformation in resource-based cities. The inhibitory effect of ER on industrial structure rationalization decreases as the severity of ER increases. There is a shift from the promotion to the restriction of industrial structure rationalization due to TI increase. In contrast, TI strengthens the optimization of industrial structure. The promotion effects of ER and TI on industrial structure optimization improve as the former and latter increase in comprehensive regional cities. The influence of TI on the industrial transformation of industry-oriented cities is consistent with its impact on resource-based cities. These findings provide theoretical guidance and inspiration for urban industrial transformation in response to ER and TI based on their functional roles.